Central Bank Communication with the Polarized Public - Pei Kuang; Michael Weber; Shihan Xie (CESifo GmbH, 2025)
This paper examines the impact of political polarization on public trust in the Fed and its influence on macroeconomic expectations. Using a large-scale survey experiment which we fielded on President Trump's 2025 inauguration day, we study how households form beliefs about the Fed regarding its political leaning, independence, and trustworthiness. Political alignment significantly shapes perceptions: individuals who view the Fed as politically aligned report higher independence of and trust in the Fed, leading to lower inflation expectations and uncertainty. Strategic communication on institutional structure and policy objectives effectively mitigates perception biases, reinforcing the Fed's credibility and enhancing its policy effectivenes.
Keywords: D83; D84; D72; E70; E31; 330; central bank communication; partisan; trust; expectations